Capital, labour and productivity: What role do they play in the potential GPD weakness of France, Germany and Italy? - Antonio Bassanetti; Jörg Döpke; Roberto Torrini; Roberta Zizza (Deutsche Bundesbank, 2006)
The paper analyses the recent supply side developments in France, Germany, and Italy by employing a non-parametric approach to estimate potential GDP. The analysis reveals marked heterogeneity among the three countries with regard to the contribution made by labour input. Where similarities can be found, however, are in the slowdown of accumulation activity and in the pronounced worsening of total factor productivity. The paper is rounded out by estimates of some measures of wage pressures and of profitability in order to assess the role played by the movements of relative input prices in the intensity of use of primary factors in the production process.
Keywords: E32; O47; O52; 330; Potential output; growth accounting; productivity; NAIRU; factor shares; Wirtschaftspotenzial; Wirtschaftswachstum; Produktivität; Produktionsfaktor; Faktorpreis; Natürliche Arbeitslosigkeit; Schätzung; Deutschland; Frankreich; Italien